A randomized placebo-controlled trial of N-acetylcysteine for cannabis use disorder in adults. (1st August 2017) - Gray, Kevin M.; Sonne, Susan C.; McClure, Erin A.; Ghitza, Udi E.; Matthews, Abigail G.; McRae-Clark, Aimee L.; Carroll, Kathleen M.; Potter, Jennifer S.; Wiest, Katharina; Mooney, Larissa J.; Hasson, Albert; Walsh, Sharon L.; et al.
Highlights: N -acetylcysteine (NAC) was evaluated for cannabis use disorder (CUD) in adults. All trial participants concurrently received contingency management (CM). NAC was previously shown to be efficacious when added to CM in adolescents. The present trial did not yield evidence of efficacy of NAC added to CM in adults. Additional work is needed to identify and optimize novel treatments for CUD. Abstract: Background: Cannabis use disorder (CUD) is a prevalent and impairing condition, and established psychosocial treatments convey limited efficacy. In light of recent findings supporting the efficacy of N -acetylcysteine (NAC) for CUD in adolescents, the objective of this trial was to evaluate its efficacy in adults. Methods: In a 12-week double-blind randomized placebo-controlled trial, treatment-seeking adults ages 18–50 with CUD ( N  = 302), enrolled across six National Drug Abuse Treatment Clinical Trials Network-affiliated clinical sites, were randomized in a 1:1 ratio to a 12-week course of NAC 1200 mg ( n  = 153) or placebo ( n  = 149) twice daily. All participants received contingency management (CM) and medical management. The primary efficacy measure was the odds of negative urine cannabinoid tests during treatment, compared between NAC and placebo participants. Results: There was not statistically significant evidence that the NAC and placebo groups differed in cannabis abstinence (odds ratio = 1.00, 95% confidence interval 0.63–1.59, p  = 0.984). Overall, 22.3% of urine cannabinoid tests in the NAC group were negative, compared with 22.4% in the placebo group. Many participants were medication non-adherent; exploratory analysis within medication-adherent subgroups revealed no significant differential abstinence outcomes by treatment group. Conclusions: In contrast with prior findings in adolescents, there is no evidence that NAC 1200 mg twice daily plus CM is differentially efficacious for CUD in adults when compared to placebo plus CM. This discrepant finding between adolescents and adults with CUD may have been influenced by differences in development, cannabis use profiles, responses to embedded behavioral treatment, medication adherence, and other factors.